Implementation Program of the School Operational Assistance: A Case Study in Berau District: A Case Study in Berau District - Dewi Sugesti; Syachrumsyah Asri; Sudirah Sudirah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
School Operational Assistance (SOA) is a government program to improve the quality and quality of learning in state schools. Yet, SOA reporting was colored by delays by various schools. Reporting must be under regional financial administration. On the other hand, schools are required to make reports according to the format from the Ministry of Education and Culture of the Republic of Indonesia. Through this paper, the author analyzes the implementation of the SOA policy at the elementary (SD) and junior high school (SMP) levels. Too, we also analyze the factors that support and hinder the implementation of the policy in public schools in Berau District. This study uses a descriptive method with a case-qualitative study. Referring to absorption capacity, effectiveness, accountability, transparency, implementer commitment, goals and targets, as well as analyzing the factors that influence SOA policy, it shows that its actualization in schools located in the city center have